Modos de ser e modos de viver : a trajetória dos estrangeiros em Natal/RN - Viana, Thereza Cristina Bertazzo Silveira (2012)
This work aims to understand the trajectory of immigrants living in Natal / RN, between the years 1990 and 2009, their motivations for this change, their sociability relations, as well as the impact of this group in Natal and specifically, in the district of Ponta Negra, where most of them established their residences or work. Considering that the historical, political, economical and social environment where these immigrants are inserted, are different from that experienced by former immigrants who came to Brazil in the late nineteenth and early twentieth centuries, a period of mass migration, it was revealed that immigration studied in contemporary Natal constitutes a new configuration (Elias, 1994). This new configuration is represented by several characteristics that distinguish this contemporary immigration, as: the relationship established by these foreigners, both with their country of origin and the destination, the formation of social networks that offer support to newcomers and those already installed, the relations of sociability with locals and a new relationship of belonging with the space, since the possibility of coming and going from one country to the other, allows a (re)production of their original ?? social and economic life in the new space. The research methodology was based on the analysis of narrative interviews, in light of the theory of Schütze (1977) in order to understand the faces of this immigration. As theoretical support for the data analysis the theories of authors such as Norbert Elias, presentedin his work about the established and outsiders, Pierre Bourdieu, and his concept of habitus, distinction and style of life, Georg Simmel, and his study of life in the metropolis, his analysis of the foreigner and his theory of sociability, among others. This study attempted to give visibility to foreigners living in Natal, who experience the dynamics of the district of Ponta Negra and reconstruct their daily relations of sociability in this space. In fact, the presence of foreigners in this urban context allows for the construction of new configurations, both in terms of the physical space of the neighborhood, which has been modified by the touristification process and the real estate market, which is molded to meet this demand, but also in their social sphere, with regard to the relations established between foreign residents and locals. In seeking to characterize these migratory experiences it could be understood that the trajectories of each foreigner is part of a broader social structure, which cannot be evaluated neither disconnected from the contexts in which they operate, nor under a single point of view